Purity, Body, and Self in Early Rabbinic Literature - Balberg, Mira, 1978- (Book collections on Project MUSE., 2014)
This book explores the ways in which the early rabbis reshaped biblical laws of ritual purity and impurity and argues that the rabbis' new purity discourse generated a unique notion of a bodily self. Focusing on the Mishnah, a Palestinian legal codex compiled around the turn of the third century CE, Mira Balberg shows how the rabbis constructed the processes of contracting, conveying, and managing ritual impurity as ways of negotiating the relations between one's self and one's body and, more broadly, the relations between one's self and one's human and nonhuman environments. With their.